The Development of Android-based Augmented Reality Learning Media in Curved Surfaces Geometry - Saragih, Atiqah Zikry Amalia; Fatimah, Siti; Suhendra, Suhendra (Universitas Suryakancana, 2024)
The increasing level of technology used in the education sector has an impact on the use of technology as a learning media. The research aims to develop and produce an android-based augmented reality learning media in curved surfaces geometry for junior high school students and to know student’s respond to the learning media. The type of this research is research and development and used the Luther-Sutopo Multimedia Development Method. Six stages to develop the android-based augmented reality learning media in geometry are concept, design, material collecting, assembly, testing and distribution. In the fifth stage, testing, the learning media tested at two steps, by validators and student’s respond. The validators gave score as much as 85.95% (valid without revision) for the content and construct materials of the learning media. The students gave good response of learning media, it can be seen from in the usefulness aspect, 70% of respondents agreed that this learning media was useful and could be used in the learning process of curved geometric shapes. For the ease of use aspect 55% of respondents agreed that this learning media was easy to use. For the ease of learning aspect 50% of respondents agreed that this learning media could help them in the process of understanding curved surfaces geometry material and for the satisfaction aspect 65% of respondents felt learning geometry with the help of learning media was fun and would recommend using this learning media to their friends.